Silent witnesses: unveiling the epidemic of femicides in North-west Tshwane, South Africa – a decade of analysis - Yaseen Bismilla; K. K. Hlaise; C. Van Wyk (BMC Public Health)
Abstract Background Femicides, defined as the gender-based killing of women, are a pressing public health issue worldwide, with South Africa experiencing some of the highest rates globally. This study focuses on the North-west region of Tshwane, particularly the Garankuwa area, aiming to address gaps in understanding the epidemiology, demographics, circumstances, and pathology associated with femicides. The Garankuwa mortuary serves as the primary site for this investigation, providing a detailed analysis over a ten-year period, shedding light on contributing risk factors in the context of systemic gender inequality. Objectives The study had four main objectives: to analyse the demographics and incidence rates of femicides in the North-west Tshwane area, to examine the circumstances surrounding femicides (including the time, location, and demographic risk factors), to identify the causes and pathological characteristics of femicides; and to observe trends in femicide rates over the ten-year study period. Methods This study was a retrospective cross-sectional descriptive analysis, focusing on all deceased females admitted to the Garankuwa mortuary from 2009 to 2018. The inclusion criteria comprised female cases at autopsy, with a suspected homicidal manner of death. Excluded were cases classified as suicides, accidents, or natural deaths after further examination. Data was collected through the National Injury Mortality Surveillance System (NIMSS) and cross-verified with post-mortem reports, police data and death registers. Results Over the ten-year period, the Garankuwa mortuary admitted an annual average of 1131 bodies, with approximately 23.5% (266) being female. Of these, 17.5% were identified as femicides. The average incidence rate of femicides was 11.2 per 100,000 female population, showing a general decline over the study period, except for notable increases in 2013 and 2016. The study found that the most common months for femicides were September and December, with most incidents occurring at home, followed by residential areas and medical facilities. The geographic analysis identified Temba, Rietgat, and Akasia as the areas with the highest number of femicide cases. Demographically, the majority of femicide victims were black, with the most affected age group being 18–39 years. The leading causes of death were gunshot wounds, sharp force injuries and blunt force trauma, with significant incidences of strangulation and asphyxial deaths, primarily affecting the neck and head regions. Conclusion This study highlights the high incidence and distinct characteristics of femicides in the North-west Tshwane area, underscoring the role of socio-economic disparities and racial demographics. The findings emphasize the necessity for targeted prevention programs, stricter firearm control measures, and community-based violence prevention strategies. The demographic data indicate that young black women are particularly vulnerable, necessitating protective and educational initiatives tailored to this group.